Understanding adaptive capacity and capacity to innovate in social-ecological systems: Applying a gender lens - Cohen, Philippa J.; Lawless, Sarah; Dyer, Michelle; Morgan, Miranda; Saeny, Enly; Teioli, Helen; Kantor, Paula (Springer, 2016)
This paper examines the social and gender differentiation of capacities to adapt and innovate. It is a qualitative study in three communities in the Solomon Islands, a developing country where rural livelihoods and wellbeing are tightly tied to agriculture and fisheries. The article finds that the five dimensions of capacity to adapt and innovate (assets, flexibility, learning, social organization, and agency) are mutually dependent. The findings are of value to those aspiring for equitable improvements to wellbeing within dynamic and diverse social–ecological systems.